Recent uptake of intermittent preventive treatment during pregnancy with sulfadoxine–pyrimethamine is associated with increased prevalence of Pfdhfr mutations in Bobo-Dioulasso, Burkina Faso. (December 2017) - Cisse, Mamoudou; Awandare, Gordon; Soulama, Alamissa; Tinto, Halidou; Hayette, Marie-Pierre; Guiguemdé, Robert
Abstract Background The impact of sulfadoxine–pyrimethamine (SP) used as intermittent preventive treatment during pregnancy (IPTp-SP) on mutant parasite selection has been poorly documented in Burkina Faso. This study sought first to explore the relationship between IPTp-SP and the presence of mutant parasites. Second, to assess the relationship between the mutant parasites and adverse pregnancy outcomes. Methods From September to December 2010, dried blood spots (DBS) were collected during antenatal care visits and at delivery from 109 pregnant women with microscopically confirmedfalciparum malaria infection. DBS were analysed by PCR–restriction fragment length polymorphism (PCR–RFLP) for the polymorphisms at codons 51, 59, 108, and 164 of thePfdhfr gene and codons 437 and 540 in thePfdhps gene. Results Both thePfdhfr andPfdhps genes were successfully genotyped in 92.7% (101/109) of the samples. The prevalence ofPfdhfr mutations N51I, C59R and S108N was 71.3, 42.6 and 64.4%, respectively. Overall, 80.2% (81/101) of samples carried thePfdhps A437G mutation. None of the samples had thePfdhfr I164L and thePfdhps K540E mutations. The prevalence of the triple mutation N51I + C59R + S108N was 25.7% (26/101). The use of IPTp-SP was associated with a threefold increased odds ofPfdhfr C59R mutation [crude OR 3.29; 95% CI (1.44–7.50)]. Pregnant women withrecent uptake of IPTp-SP were at higher odds of both thePfdhfr C59R mutation [adjusted OR 4.26; 95% CI (1.64–11.07)] and thePfdhfr intermediate-to-high resistance, i.e.,  ≥ 2Pfdhfr mutations [adjusted OR 3.45; 95% CI (1.18–10.07)]. There was no statistically significant association between the presence of thePfdhfr intermediate-to-high resistance and parasite densities or both maternal haemoglobin level and anaemia. Conclusion The data indicate that despite the possibility that IPTp-SP contributes to the selection of resistant parasites, it did not potentiate pregnancy-associated malaria morbidity, suggesting the continuation of SP use as IPTp in Burkina Faso.